Burkholderia pseudomallei type III secreted protein BipC: role in actin modulation and translocation activities required for the bacterial intracellular lifecycle - Kang,Wen Tyng; Vellasamy,Kumutha Malar; Rajamani,Lakshminarayanan; Beuerman,Roger W.; Vadivelu,Jamuna (PeerJ, 2016)
Melioidosis, an infection caused by the facultative intracellular pathogen Burkholderia pseudomallei, has been classified as an emerging disease with the number of patients steadily increasing at an alarming rate. B. pseudomalleipossess various virulence determinants that allow them to invade the host and evade the host immune response, such as the type III secretion systems (TTSS). The products of this specialized secretion system are particularly important for the B. pseudomallei infection. Lacking in one or more components of the TTSS demonstrated different degrees of defects in the intracellular lifecycle of B. pseudomallei. Further understanding the functional roles of proteins involved in B. pseudomallei TTSS will enable us to dissect the enigma of B. pseudomallei-host cell interaction. In this study, BipC (a translocator), which was previously reported to be involved in the pathogenesis of B. pseudomallei, was further characterized using the bioinformatics and molecular approaches. The bipCgene, coding for a putative invasive protein, was first PCR amplified from B. pseudomallei K96243 genomic DNA and cloned into an expression vector for overexpression in Escherichia coli. The soluble protein was subsequently purified and assayed for actin polymerization and depolymerization. BipC was verified to subvert the host actin dynamics as demonstrated by the capability to polymerize actin in vitro. Homology modeling was also attempted to predict the structure of BipC. Overall, our findings identified that the protein encoded by the bipC gene plays a role as an effector involved in the actin binding activity to facilitate internalization of B. pseudomalleiinto the host cells.
Keywords: Burkholderia pseudomallei; Type III secretion system; Effector protein; Intracellular lifecycle; Protein expression and purification; Actin dynamics